Numerical modeling of strongly coupled microscale multiphase flow and solid deformation. (26th November 2019) - Fagbemi, Samuel; Tahmasebi, Pejman; Piri, Mohammad
Summary: When fluid flows in porous media under subsurface conditions, significant deformation can occur. Such deformation is dependent on structural and phase characteristics. In this paper, we investigate the effect of multiphase flow on the deformation of porous media at the pore scale by implementing a strongly coupled partitioned solver discretized with finite volume (FV) technique. Specifically, the role of capillary forces on grain deformation in porous media is investigated. The fluid and solid subdomains are meshed using unstructured independent grids. The model is applied for solving multiphase coupled equations and is capable of capturing pore scale physics during primary drainage by solving the Navier‐Stokes equation and advecting fluid indicator function using volume of fluid (VOF) while the fluid is interacting with a nonlinear elastic solid matrix. The convergence of the coupled solver is accelerated by Aitken underrelaxation. We also reproduce geomechanical stress conditions, at the pore scale, by applying uniaxial stress on the solid while simultaneously solving the multiphase fluid‐solid interaction problem to investigate the effect of external stress on fluid occupancy, velocity‐field distribution, and relative permeability. We observe that the solid matrix exhibits elasto‐capillary behavior during the drainage sequence. Relative permeability endpoints are shifted on the basis of the external stress exerted.